The Effect of Handedness and Gender on Performance in Cognitive Ability Tasks - Sharda, Meeshita (My University, 2023)
Handedness refers to the dominant hand an individual uses to perform daily tasks, which can be left or right. This phenomenon has been the subject of extensive research, as it has been linked to differences in brain lateralization and cognitive functioning. The impact of Handedness on cognitive performance has been studied using a variety of performance tasks, including motor skills, memory, language, spatial reasoning, speed, executive function, and many more. The current study investigates the Effect of Handedness and Gender on the performance of Cognitive Ability Tasks. For this purpose, a sample of 29 Left-handers and 31 Right-handers in the age range of 16 to 30 years was obtained. The Standardized measures administered to participants were: Handedness Inventory, 3-Dimensional space perception (Subscale of GATB) for Spatial Ability, Digit Symbol Search Test for Motor Speed, and Trail Making Test for Executive functioning. Data were analyzed using SPSS, through which Descriptive Statistics, Independent T-Test, and ANOVA were computed. The results show a significant difference in the performance of left-handers and right-handed individuals in various Cognitive tasks. It also shows that there is no significant gender difference.
Keywords: Handedness; Spatial Ability; Motor speed, and Executive Functioning